Association of cleft palate and craniofacial syndromic anomalies with the outcome of tympanostomy tube insertion and time to recovery from recurrent otitis media with effusion - Kitirat Ungkanont; Alisa Tabthong; Chulaluk Komoltri; Vannipa Vathanophas; Archwin Tanphaichitr; Phawin Keskool (Elsevier, 2021)
This research was aimed to study the association of cleft palate and craniofacial syndromic anomalies with the outcome of the tympanic membrane after tympanostomy tube insertion and time to recovery from recurrent otitis media with effusion. A retrospective cohort study was done in 85 children with cleft palate and 102 non-cleft children who had tympanostomy tube insertion for otitis media with effusion. The desired outcome was the recovery of recurrent otitis media with effusion with intact tympanic membrane. Craniofacial syndromic anomalies were found in 11.8% of the children in both groups. Intact tympanic membrane was found most commonly in noncleft children without craniofacial anomalies (63.7%). Cleft palate was the most significant risk for the non-intact tympanic membrane after adjusting for syndromic anomalies and the number of tympanostomy tube insertion (p = 0.047). Time to recovery from recurrent otitis media with effusion was shortest in the non-cleft children without craniofacial anomalies (4.9 years) with the highest probability of cure (hazard ratio and 95% CI 3.46 (1.62, 7.39)). Children with cleft palate had higher probability of cure than the children with cleft palate and craniofacial syndromic anomalies (hazard ratio and 95% CI 2.59 (1.16, 5.80)). Children with cleft palate and craniofacial syndromic anomalies had highest incidence of otorrhea (59.1%) and repeated tympanostomy tube insertion (86.4%). Craniofacial syndromic anomalies with cleft palate contributed to a longer time to recovery and higher incidence of complications from tympanostomy tube.